Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/ie800061q
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Isomerization of Butene in Fixed Beds. 1. Experimental Investigation and Structure−Performance Effects

Abstract: An experimental investigation of structure-performance effects in zeolite catalyzed skeletal isomerization has been carried out. Two structurally different, medium-pore-size zeolites (H-TON and H-FER) with similar acidities were compared in butene skeletal isomerization. While both catalysts proved to be efficient in the test reaction, their deactivation behavior differed substantially. H-FER exhibited significantly higher initial isobutene yields and selectivities, and the catalyst performance was also more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Proton-exchanged zeolites play an important role in the petrochemical industry, fine chemical production, and oil refining. Based on the acidity of their Brønsted sites, they are successfully used as catalysts for a range chemical reactions. One application is hydrocarbon transformation reactions such as skeletal isomerization of linear alkenes. The activity of zeolites in this reaction is based on their ability to donate a proton to alkenes, forming positively charged carbenium ions as transition structures or intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Proton-exchanged zeolites play an important role in the petrochemical industry, fine chemical production, and oil refining. Based on the acidity of their Brønsted sites, they are successfully used as catalysts for a range chemical reactions. One application is hydrocarbon transformation reactions such as skeletal isomerization of linear alkenes. The activity of zeolites in this reaction is based on their ability to donate a proton to alkenes, forming positively charged carbenium ions as transition structures or intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Three possible mechanisms have been proposed for the skeletal isomerization of hydrocarbon, monomolecular, , bimolecular, and pseudo-monomolecular mechanisms. Among these three mechanisms, the monomolecular mechanism is currently considered to be the predominant mechanism for the isomerization, whereas the bimolecular mechanism is mainly responsible for the formation of byproducts. , …”
Section: Resultsmentioning
confidence: 99%
“…101 Most authors seem to converge today on the monomolecular mechanism. 102,103 On the other hand, it has been shown that monobranched compounds may diffuse much better in the 10 MR larger channels of FER structure than in the 8 MR smaller ones, where access of branched compounds is strongly hindered. 92 Compounds with the tert-butyl group appear to be unallowed to enter both channels, at least at room temperature.…”
Section: Ferrierite (H-fer)mentioning
confidence: 99%